STRESS RATE PROFILE AND COPING MANAGEMENT TYPE AMONG STUDENTS IN COVID-19 PANDEMIC CONDITION (Proceedings of the Global Public Health Conference, 2021)
Coronavirus Disease 2019 (COVID-19) has changed people’s habits nowadays. Everyaspect of daily living was affected, mainly by people’s health, economy, politics, national defensefor the macro problems, and the micro problems such as the social living of human beings andpsychological aspect of an individual. COVID-19 brings difficult conditions for almost all of thepeople in the world. The hard condition can make an individual become stressed and have to adapt tothe situation by doing the coping strategies. This research aims to find the profile of stress rate, thenthe source of the stress condition, type of coping managements and coping have been done as copingstrategies that have been done by Universitas Airlangga Students in COVID-19 pandemic condition.This research is descriptive research conducted on Universitas Airlangga students around September– October 2020. This cross-sectional research was to collect the information by using a questionnairewith a total of 45 questions. The number of samples is 121 respondents with criteria as an activeUniversitas Airlangga student in bachelor degree. The information was collected then analyzed withthe SPSS application. From this research, we know that from 121 respondents as UniversitasAirlangga students, most of them had a moderate stress level (74%), followed by a high perceivedstress level (23%), and a low level (3%). Then, the coping managements that have been done bythem majority doing the problem-focused coping to adapt with the stress condition and the copingstrategies that have been done in COVID-19 pandemic condition is following health protocol as thegovernment policy.
Keywords: stress profile; coping management; students; COVID-19